REMINISCENCE CAN BE MISLEADING - Orpen, N.D. (Scientia Militaria - South African Journal of Military Studies, 2012)
As a full-time military historian, I have found Militaria a most valuable source and invariably interesting, but after reading the 'Herinneringe' of so well-known a soldier as General 'Matie' du Toit in your issue No 10/2 of 1980, I feel that it is only fair to draw attention of all serious students of history to the fact that reminiscences cannot be entirely relied upon unless they are very carefully checked and sub-edited before publication.